Experience with successful treatment of severe recurrent vulvar adhesions: A case report - Bi, Yingying; Chen, Yuhang; Li, Wu; Jiang, Huici; Qin, Jinlong; Cheng, Jiajing (Frontiers in Surgery, 2023)
Vulvar adhesions are defined as partial or complete adherence of the labia minora and/or labia majora. Vulvar adhesions are rare, especially in postmenopausal women.This article describes a case of postmenopausal recurrent vulvar adhesions successfully treated with surgery. The patient was a 52-year-old woman who had undergone manual separation and surgical adhesion release due to vulvar adhesions, which recurred soon after treatment. The patient then came to our hospital for treatment because of complete dense adhesions to the vulva and laboured urination. The patient received surgical treatment, the anatomical structure of the vulva recovered well, and the symptoms affecting the urinary system disappeared. There was no readhesion during the 3-month follow-up.